Synthesis of 3,3′-Bis(diphenylphosphine)-2H,2′H-4,4′-bichromenes: Novel Bidentate Diphosphine Ligands - Mai, Jiaqian; Chen, Lvshuang; Haiyang, Huang; Bao, Hongli (Synthesis)
Bidentate diphosphine ligands play a crucial role in metalcatalyzed organic synthesis, yet the structural diversity of existing ligands remains limited. This study reports a novel class of bidentate diphosphine ligands featuring a 2H,2′H-4,4′-bichromene skeleton-a similar framework to classical binaphthalene. These ligands were efficiently synthesized via a Pd-catalyzed C-P cross-coupling reaction.Characterization of their metal complexes revealed adaptable coordination geometries due to the ligand's inherent flexibility. The utility of this ligand system was demonstrated by its enhanced performance over BINAP in a sterically hindered Suzuki-Miyaura coupling, highlighting its potential in catalysis.